Kinerja Pompa Air Dc Berdasarkan Intensitas Tenaga Surya - Saputra, Fitriadi; , Hasyim Asy'ari, ST.MT; , Agus Supardi, S.T., M.T (2015)
Increasing the electrical energy needs of human attempts to exploit the energy resources of consumables is increasing. Given the limited supply of energy resources, then began to look for other energy sources such as solar energy, wave energy, wind energy, tidal energy, and other energy. Today the use of solar cells are increasingly being developed as an alternative source of power generation. This study aims to determine the performance of pump water using solar power, and the observations made are related to the depth of the water source, the intensity of the resulting solar cells, and the resulting water discharge water pump. Who carried out the research and analysis shows that the water pump to obtain the highest discharge when the source water at a depth of 1 meter, with output of as much as 21 liters of water per minute. low water discharge is when the water source is located at a depth of 3 meters, with output of as much as 19 liters of water. Longest working water pump that is when the light intensity 82 200 LUX at a depth of 1 meter, can work for 3,90menit. Inversely when the light intensity 0 LUX at a depth of 3 meters, just mamperoleh time of 2.34 minutes, this was due to the intensity of the light will also help supply the battery charge or batteries.